2006
DOI: 10.1002/ajmg.b.30363
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of linkage and association on 18p11.2 for psychosis

Abstract: The genetic basis of bipolar disorder (BPD) and schizophrenia (SCZ) has been established through numerous clinical and molecular studies. Although often considered separate nosological entities, evidence now suggests that the two syndromes may share some genetic liability. Recent studies have used a composite phenotype (psychosis) that includes BPD, SCZ, psychosis not otherwise specified, and schizoaffective disorder, to identify shared susceptibility loci. Several chromosomal regions are reported to be shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The search was performed in pub med for every chromosome separately with the key words: “Bipolar disorder, genetics, linkage, chromosome 1…X” and “Migraine, genetics, linkage, chromosome 1…X”, Table 3 displays all linkage loci that have been significantly or suggestively found in migraine linkage studies (Gardner et al, 1997; Nyholt et al, 1998a,b, 2000; Jones et al, 2001; Carlsson et al, 2002; Wessman et al, 2002; Lea et al, 2002; Björnsson et al, 2003; Soragna et al, 2003; Cader et al, 2003; Nyholt et al, 2005; Russo et al, 2005; Lea et al, 2005; Anttila et al, 2006), and the bipolar linkage studies (Savitz et al, 2007; Jamra et al, 2007; Zandi et al, 2007; Goes et al, 2007; Cassidy et al, 2007; Kerner et al, 2007; Jones et al, 2007; Etain et al, 2006; Marcheco-Teruel et al, 2006; Tomàs et al, 2006; Mukherjee et al, 2006; Schumacher et al, 2005; Hamshere et al, 2005; Lambert et al, 2005; McQueen et al, 2005; Kealey et al, 2005; Lin et al, 2005; Macgregor et al, 2004; Middleton et al, 2004; Fallin et al, 2004; Curtis et al, 2003; McInnis et al, 2003; Willour et al, 2003; Ewald et al, 2003; Ekholm et al, 2003; Ewald et al, 2002; Ekholm et al, 2002; Bailer et al, 2002; Dick et al, 2002; Cichon et al, 2001; Kelsoe et al, 2001; Radhakrishna et al, 2001; Detera-Wadleigh et al, 1999; Morissette et al, 1999; Ginns et al, 1998; Ewald et al, 1998; Detera-Wadleigh et al, 1997; Edenberg et al, 1997; Blackwood et al, 1996; Turecki et al, 1995; Pekkarinen et al, 1995) that have demonstrated overlapping or closely related linkage to these migraine loci. In addition we compared linkage studies in BPAD to the identified genes in FHM, and the BPAD (Jamra et al, 2007; Zandi et al, 2007; Hamshere et al, 2005; Middleton et al, 2004; Fallin et al, 2004; …”
Section: Discussionmentioning
confidence: 99%
“…The search was performed in pub med for every chromosome separately with the key words: “Bipolar disorder, genetics, linkage, chromosome 1…X” and “Migraine, genetics, linkage, chromosome 1…X”, Table 3 displays all linkage loci that have been significantly or suggestively found in migraine linkage studies (Gardner et al, 1997; Nyholt et al, 1998a,b, 2000; Jones et al, 2001; Carlsson et al, 2002; Wessman et al, 2002; Lea et al, 2002; Björnsson et al, 2003; Soragna et al, 2003; Cader et al, 2003; Nyholt et al, 2005; Russo et al, 2005; Lea et al, 2005; Anttila et al, 2006), and the bipolar linkage studies (Savitz et al, 2007; Jamra et al, 2007; Zandi et al, 2007; Goes et al, 2007; Cassidy et al, 2007; Kerner et al, 2007; Jones et al, 2007; Etain et al, 2006; Marcheco-Teruel et al, 2006; Tomàs et al, 2006; Mukherjee et al, 2006; Schumacher et al, 2005; Hamshere et al, 2005; Lambert et al, 2005; McQueen et al, 2005; Kealey et al, 2005; Lin et al, 2005; Macgregor et al, 2004; Middleton et al, 2004; Fallin et al, 2004; Curtis et al, 2003; McInnis et al, 2003; Willour et al, 2003; Ewald et al, 2003; Ekholm et al, 2003; Ewald et al, 2002; Ekholm et al, 2002; Bailer et al, 2002; Dick et al, 2002; Cichon et al, 2001; Kelsoe et al, 2001; Radhakrishna et al, 2001; Detera-Wadleigh et al, 1999; Morissette et al, 1999; Ginns et al, 1998; Ewald et al, 1998; Detera-Wadleigh et al, 1997; Edenberg et al, 1997; Blackwood et al, 1996; Turecki et al, 1995; Pekkarinen et al, 1995) that have demonstrated overlapping or closely related linkage to these migraine loci. In addition we compared linkage studies in BPAD to the identified genes in FHM, and the BPAD (Jamra et al, 2007; Zandi et al, 2007; Hamshere et al, 2005; Middleton et al, 2004; Fallin et al, 2004; …”
Section: Discussionmentioning
confidence: 99%
“…Some of the families in the cohort have been on follow up for longer than 10 years. We have previously noted evidence of linkage in psychosis at chromosome 18p11.2, and the sex‐specific association to the DISC1 gene using a case–control study design in samples taken from this cohort. For the current study, eight families (A through H) with high loading of SMI (SCZ, BD, and psychosis in the context of these eight pedigrees; Fig.…”
Section: Methodsmentioning
confidence: 68%
“…Many studies reported that susceptibility genes may be present on chromosome 18p where the PACAP gene is located [86][87][88][89][90][91] . A possible linkage of certain psychiatric diseases with the PACAP gene Adcyap1 has been suggested.…”
Section: Genetic Association Of Pacap and Pac1 To Major Mental Illnessesmentioning
confidence: 99%